Manufacturing of AA6061 propeller for AUV application using cold forging process - Abdullah, Ahmad Baharuddin; Salit, Mohd Sapuan; Samad, Zahurin; Tandur, Khaleed Hussain M.; Abdul Aziz, Nuraini (Academic Journals, 2012)
Recently, faster and energy saving propeller have become the focus of attention in the marine industry. Furthermore, changeability of the blade is also taken into account for faster replacement and repair works. The objective of the paper is to present the error assessment of the designed Autonomous Underwater Vehicle(AUV) propeller blade. The paper briefly discusses the design steps involved including optimization and fabrication process. The error is assessed based on geometrical and dimensional accuracy of the forged blade utilizing the conventional measurement equipment and finite element analysis. The discussion is focused on the error caused by the manufacturing process. The error was measured based on the thickness and twist angle deviation as compared with the nominal model. The error committed during the assembly in the pin head is also presented.